A study to assess mass drug administration of DEC for filaria control in district Satna, Madhya Pradesh: a mid term assessment - Sharma, Vivek; Kabirpanthi, Vikrant (International Journal Of Community Medicine And Public Health, 2018)
Background: Lymphatic filariasis is a major public health problem which is caused by Wuchereria Bancrofti and Brugia Malai. The disease is endemic in 250 districts in 20 states and UTs. In India national health policy 2002 envisages elimination of lymphatic filariasis by 2015. Important strategy for elimination of lymphatic filariasis is through annual mass drug administration of single dose of DEC for 5 year or more to the eligible population. Present cross sectional study was carried out to assess drug compliance after mass drug administration of DEC and the factors responsible for poor compliance among the population of Satna district of MP. Methods: The present study was a cross-sectional study which was carried out in filarial endemic Satna district. In this district 120 houses from 3 CHC & one urban ward was randomly selected. 30 households each from 3 rural and one urban site were interviewed related to MDA for DEC. Results: Coverage of tablet distribution in Satna was 90.9%. Consumption of drug among the people who received the drug was 87.97%, while the total effective consumption was 79.9%. Drug distributors ensured consumption of drug in only 16.9%. Conclusions: Focus of MDA is primarily to mere distribution of drug. There is need to give emphasis on consumption of drug, health education, common side effects and its management in order to increase effective coverage rate.